2023
DOI: 10.1186/s43141-023-00471-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of exopolysaccharide produced by Streptomyces rochie strain OF1 and its effect as ameliorative on osteoarthritis in rats via inhibiting TNF-α/COX2 pathway

Abstract: Background Carbohydrates are known as the main natural products of life activities. Results Streptomyces rochie strain OF1 isolated from a mangrove tree produced exopolysaccharide S5 (EPSS5) (14.2 gl−1) containing uronic acid 21.98% sulfate content of 11.65 mg/ml, and a viscosity of 1.35 mm2/s. while total hexose amine content was 24.72%. The high performance liquid chromatography (HPLC) analysis of mono sugars revealed that EPS was composed of man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This might have been as a result of a lower concentration used than would record signi cant biocontrol activity. A study reported by Mohamed et al [45] on exopolysaccharide (EPSS5) produced from Streptomyces rochie strain OF1 documented its middling antibiotic activity against strains of Escherichia coli ATCC 25922 and Staphylococcus aureus NRRLB-767 worked on. In addition, the exopolysaccharide exhibited little antibacterial activity against Klebsiella pneumoniae ATCC 10145 and methicillin-resistant Staphylococcus aureus strains used in their research.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been as a result of a lower concentration used than would record signi cant biocontrol activity. A study reported by Mohamed et al [45] on exopolysaccharide (EPSS5) produced from Streptomyces rochie strain OF1 documented its middling antibiotic activity against strains of Escherichia coli ATCC 25922 and Staphylococcus aureus NRRLB-767 worked on. In addition, the exopolysaccharide exhibited little antibacterial activity against Klebsiella pneumoniae ATCC 10145 and methicillin-resistant Staphylococcus aureus strains used in their research.…”
Section: Discussionmentioning
confidence: 99%
“…The major yield fraction obtained by 1 volume of absolute ethanol was dried under vacuum at 40 °C 59 . The UV absorption spectrum was recorded using a UV–Vis Spectrophotometer (2401PC Shimadzu, Japan) between 200 and 800 nm, to examine the existence of proteins and nucleic acids 3 . The main fraction of EPS from 1 volume ethanol (BMEPS) was assayed in-vitro against Acetylcholinesterase inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, EPSs are frequently utilized as viscosifying, stabilizing, gelling, or emulsifying agents in the food industry because of their distinctive physical and rheological qualities 2 . Microbial polysaccharides are incorporated into new targets, such as bioflocculants, bio absorbents, heavy metal removal, and drug delivery agents 3 . Additionally, antitumor, antiviral, immunostimulatory, and anti-inflammatory actions are among the biological effects of EPSs 4 .…”
mentioning
confidence: 99%
“…The results showed that the Streptomyces strains that produced the anti-Candida derivatives came from the most diverse environments. These included 16 studies collecting strains from distinct soil sediment samples [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 11 studies obtaining strains from lakes, seas and oceans [59][60][61][62][63][64][65][66][67][68][69][70], and 5 studies isolating them from marine sponges. Additionally, one study derived strains from marine corals [71], while insects such as wasps, ants and cockroaches contributed isolates in five studies [72][73][74][75][76].…”
Section: Streptomyces-derived Compounds With Anti-candida Activity De...mentioning
confidence: 99%